2020
DOI: 10.26434/chemrxiv.12003930.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of FDA Approved Drugs Targeting COVID-19 Virus by Structure-Based Drug Repositioning

Abstract: <p>The new strain of Coronaviruses (SARS-CoV-2), and the resulting Covid-19 disease has spread swiftly across the globe after its initial detection in late December 2019 in Wuhan, China, resulting in a pandemic status declaration by WHO within 3 months. Given the heavy toll of this pandemic, researchers are actively testing various strategies including new and repurposed drugs as well as vaccines. In the current brief report, we adopted a repositioning approach using insilico molecular modeling screening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 3 publications
0
21
0
Order By: Relevance
“…2) were identified as potential candidate treatments of patients with COVID-19, in this study. The remaining seven drugs, including hydroxychloroquine, chloroquine, disulfiram, montelukast sodium, atazanavir, indinavir, and maribavir, were also proposed as potential candidate treatments for patients with COVID-19 in previous studies (6,9,(36)(37)(38). However, within these seven drugs, only disulfiram and atazanavir were previously identified as SARS-CoV-2 M pro inhibitors, whereas the other five drugs were either reported to be active in vitro against SARS-CoV-2 without knowing the specific targets or predicted by computational modeling only without knowing their actual experimental activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2) were identified as potential candidate treatments of patients with COVID-19, in this study. The remaining seven drugs, including hydroxychloroquine, chloroquine, disulfiram, montelukast sodium, atazanavir, indinavir, and maribavir, were also proposed as potential candidate treatments for patients with COVID-19 in previous studies (6,9,(36)(37)(38). However, within these seven drugs, only disulfiram and atazanavir were previously identified as SARS-CoV-2 M pro inhibitors, whereas the other five drugs were either reported to be active in vitro against SARS-CoV-2 without knowing the specific targets or predicted by computational modeling only without knowing their actual experimental activity.…”
Section: Resultsmentioning
confidence: 99%
“…The discrepancy between the K i and EC 50 values may be attributed to the possibly imperfect intracellular drug bioavailability such that the intracellular drug concentration is different from the externally added drug concentration. Table 1 (6,36); hydroxychloroquine, chloroquine, and indinavir were reported to be active in vitro against SARS-CoV-2, but their molecular targets were not reported (9,37,39); montelukast sodium and maribavir were only predicted by calculations (37,38) without experimental activity data reported. Disulfiram and atazanavir served as the positive controls for the in vitro activity [in the literature, the IC 50 values for disulfiram and atazanavir were 9.35 and 10 μM, respectively (6,36), and the results of our test were 4.7 and 7.5 μM, respectively, when the same substrate concentration of 20 μM was used].…”
Section: Molecular Mechanism For the Antiviral Activity Of Chloroquinmentioning
confidence: 99%
“…The development of novel compounds or vaccines that work correctly against SARS-CoV-2 is a time-consuming process. Thus, efforts are focusing on repurposing the use of drugs available on the market to act against SARS-CoV-2 [65][66][67]. Chloroquine and hydroxychloroquine stand as excellent examples and are being adopted at the moment in the standard clinical practices of China for SARS-CoV-2 infection [27].…”
Section: Current Treatments Adapted To Manage the Diseasementioning
confidence: 99%
“…It is being evaluated in the U.S. alone (NCT04456153; n = 60) or in combination with azithromycin in an open-label, non-randomized study in COVID-19 patients at HonorHealth Clinical Research Institute, U.S. (NCT04339426; n = 25). One potential mechanism of action for atovaquone pertaining to SARS-CoV-2 is the inhibition of M pro [ 221 ]. Another computational study suggested that it may inhibit RdRp [ 169 ].…”
Section: Miscellaneous Antiviral Agentsmentioning
confidence: 99%